Solutions to lighten the building in the direction of stability against earthquakes (Scientific Journal of Research Studies in Future Civil Engineering, 2023)
Stylization of building is one of the new topics in construction science, which is expanding and progressing day by day. Stylization can be considered as a way to reduce the finished weight of the building by using new techniques of making new building materials and optimizing execution methods. Reducing the weight of the building, in addition to saving costs, time and energy, also reduces the losses caused by natural disasters such as earthquakes and minimizes the damage caused by the heavy weight of the building. With the advancement of technology and the availability of different, economical and optimal raw materials, executive engineers are trying to use new construction materials to stylize the building. The results of the studies conducted in this field indicate that a major part of the topics related to styling and common techniques regarding achieving the appropriate construction weight include, knowledge of common lightweight materials in the construction industry and the technology of their use, criteria Evaluating the effectiveness of these materials as light materials and the impact on the cost and weight of these materials is required for the implementation of these materials in order to be stable against earthquakes.